Starch-Based Pickering Emulsions for Bioactive Compound Encapsulation: Production, Properties, and Applications - Corrêa Ramos, Giselle Vallim (2025)
This review explores the extensive literature on starch particle-stabilized Pickering emulsions for encapsulating bioactive compounds in food products. These emulsions offer superior stability and unique properties for delivering bioactive compounds (such as polyphenols, carotenoids, fatty acids, and vitamins) in food systems such as sauces, dairy products, and functional foods. Encapsulation preserves the bioactivity of these compounds and enhances targeted delivery, offering potential nutritional and health benefits. Starch, although naturally hydrophilic and requiring modifications to enhance its functionality, is gaining increasing attention as a particle for stabilizing Pickering emulsions in foods systems. Various modifications, including chemical and structural changes, affect the functionality of starch in emulsions. This review discusses the key factors influencing emulsion stabilization, including particle and oil characteristics, as well as production methods, such as mechanical techniques. Research on the encapsulation of bioactive compounds using starch-stabilized emulsions and methods for their characterization are also presented. This review further identifies areas requiring more research, including alternative particle modification techniques, emulsion responses to external stimuli (pH, temperature), interactions between bioactive compounds and particles, their effects on digestion and nutrition, and the production of double emulsions for enhanced bioactive compound delivery.